1986
DOI: 10.1007/bf02035113
|View full text |Cite
|
Sign up to set email alerts
|

Width of the presacral space in nigerian adults

Abstract: The width of the presacral space and the thickness of the rectal valve were measured on lateral radiographs obtained during barium enema examinations performed on 182 Nigerian adult patients over a 5-year period (1980-1984). The mean width of the presacral space was 0.78 cm, the value in men being significantly higher than in women (p less than 0.01). Although these values are similar to those reported among Caucasians, a wider range of normal values was obtained in this study. There is also no significant dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 9 publications
1
7
1
Order By: Relevance
“…The results of the study carried out by Oto et al confirmed the presence of a sex difference in the width of the presacral space on MRI in a Caucasian population and also indicated that the presacral space is wider in men than in women (6). This finding was described previously in a Nigerian population (9). In that study, the width of the presacral space was measured in 182 Nigerian adult patients on lateral radiographs obtained during barium enema examinations and found to be significantly larger in men.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the study carried out by Oto et al confirmed the presence of a sex difference in the width of the presacral space on MRI in a Caucasian population and also indicated that the presacral space is wider in men than in women (6). This finding was described previously in a Nigerian population (9). In that study, the width of the presacral space was measured in 182 Nigerian adult patients on lateral radiographs obtained during barium enema examinations and found to be significantly larger in men.…”
Section: Discussionsupporting
confidence: 90%
“…These figures are slightly higher compared to those reported in the literature (Teplick et al, 1978;Akamaguna and Odita, 1986). This is almost certainly because in all of the studies in the literature the presacral space was measured while the rectum was distended by barium, whereas in our study the rectum was empty.…”
Section: Discussioncontrasting
confidence: 80%
“…This finding was described previously in a Nigerian population (Akamaguna et al, 1986). In that study, the width of the presacral space was measured in 182 Nigerian adult patients on lateral radiographs obtained during barium enema examinations and found to be significantly larger in men.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The pararectal space is found between the uterosacral and cardinal ligaments and the presacral fascia. Controversies still exist among radiologists and anatomists, however, regarding mal, although the width may vary depending on rectal filling and the patient's clinical status and sex (70,73,74).…”
Section: Pararectal Spacementioning
confidence: 99%